Renewable, Clean Energy: The Petroleum Footprint. Wind Farms Under Analysis - Matta, Elias Jorge (2012)
This paper presents a methodology to assess projects for the generation of clean, renewable energy. Such methodology is applied here to estimate the consumption of fossil fuels (referred to as ?oil?), required for the construction, operation and maintenance of a wind farm consisting of 97 turbines of 3 MW each. Results show that such consumption represents a conservative 8?9% of the total energy generated by the farm in 20 years of useful life. The need to include in the efficiency of the farm the ?unavoidable unintentional damage? to the population and its habitat, caused primarily by emissions related to the oil consumed is posed. Even though the efficiency of the wind farm is really acceptable as well as likely to be improved, the oil footprint is worryingly high. This raises serious questions as to the efficiency and feasibility of other renewable energy, particularly regarding the production of biofuels.